Pengoptimalan Manajemen Wakaf Produktif Dalam Mendorong Terwujudnya Sustainable Development Goals (SDGs) - Zunaidi, Arif; Rizqiyyah, Rifdah Nazilatul; Nikmah, Fika Kemala; Maghfiroh, Fachrial Lailatul (LPPM Universitas Trunojoyo Madura, 2023)
The purpose of this community service is to increase students' understanding, skills, and participation in managing productive waqf as an instrument for achieving sustainable development. The training was held at the Unwaha Jombang and IAIN Kediri campuses, involving a total of 80 participants. The methods used in this training include delivering relevant materials, case studies, group discussions, field practice, and visits to productive waqf institutions. During the training, participants are given an in-depth understanding of the concepts of productive waqf, financial management, reporting, and evaluation. They are also involved in field practice to apply the knowledge they have acquired to actual productive waqf management. The evaluation results show that this training succeeded in increasing participants' understanding of productive waqf and the importance of the role of students in pushing for the realization of the SDGs. In addition, participants also develop practical skills in managing waqf assets and formulating sustainable business plans. This training also encourages collaboration and networking between students, lecturers, and related institutions to create synergies in the development of productive waqf.